The effectiveness of Solution Focused Brief Counseling to improve the self-concept of commercial sex workers in rehabilitation institutions - Arif Setiawan; Yarmis Syukur; Netrawati Netrawati (Universitas Negeri Padang, 2021)
The life of the Indonesian people is a very complex life with various social problems that hit several communities. The existence of various social problems faced by the community makes them live an abnormal or inappropriate life such as the low economy in meeting the needs of life. Social problems are some conditions that arise from a society that cannot function properly, resulting in disappointment and suffering. In this case, those who often experience social problems are usually women, one of the people with social welfare problems, namely Commercial Sex Workers. Someone who works and acts in the field of prostitution is better known as a commercial sex worker. The practice of prostitution by sex workers causes several psychological impacts that refer to negative self-concepts, such as feeling of having low self-esteem in the eyes of the community, being inferior in front of many people, limiting themselves in community interactions, feeling depressed, relationship gaps with other family members. Based on the results of the study, there were 8 PSKs whose self-concept level was in the medium category with a percentage of 38.1%, then 10 PSKs whose self-concept level was in the low category, namely 47.6%. 2 PSKs whose self-concept level was in the very low category, namely 9.5%. So it can be concluded that the average self-concept of CSWs before being given treatment was in the medium and low categories. The research method used by the researcher is the experimental research method. The type of experimental research used by the researcher is a quasi-experimental (quasi-experimental). Quasi-experimental is a quasi-experiment that aims to predict the conditions that can be achieved through actual experiments, but there is no control and manipulation of all relevant variables. Based on the description above, it can be concluded that this study seeks to determine how high the self-concept of sex workers is